Sistem Informasi Pengukuran Uji Kompetensi Karyawan Berbasis Website Pada PT Surya Toto Indonesia Tbk Kabupaten Tangerang - Muhammad Rachman Mulyandi; Rizqi Eka Saputri (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2017)
Competence is one very important factor in PT Surya Toto Indonesia, with its competence then it can help companies to know the development of employee performance. The need for a computerized information system into the runway he designed this system. Redesign this system because of the execution of written competency test runs are currently still in the form of paper and the assessment process manually, so that the results obtained from the competency test is effective and efficient. With the new system, can provide information a more effective and accurate for the company in employee competence measurement. As for the research methods used in this study is a methodology literature study, observation and interviews. The results obtained from this system include HRD no longer provide value manually but by the system, and speed up the HRD in reporting results of competence. In addition, this system can also facilitate employees in a direct result of knowing the values of competency.